A single-center study of the profile of spontaneous coronary artery dissection in acute coronary syndrome patients - Harsha Basappa; Sachin T Rao; K S Sadananda; Srinidhi Hegde; C N Manjunath (Journal of Indian College of Cardiology, 2020)
Background: Spontaneous coronary artery dissection (SCAD) is rarely encountered as a primary cause of acute coronary syndrome (ACS). There is a paucity of studies involving SCAD, especially in the Indian population. Aims: We aim to study the clinical and angiographic characteristics and in-hospital outcomes of ACS patients whose angiogram incidentally shows SCAD as the cause of ACS and the management strategies opted. Methods: This is a prospective and retrospective observational study. All coronary angiograms of patients with ACS, either ST-segment elevation myocardial infarction (STEMI) or unstable angina non-STEMI, underwent within 72 h of admission, were analyzed and those patients with Saw classification Type I SCAD were included in the study. Clinical and angiographic characteristics, in-hospital outcomes, and management strategies of patients with SCAD were recorded. Results: Of the total 70 cases with SCAD included in the study, 66 (94.28%) were male. Smoking was the most common risk factor seen in 22 (31.4%) cases. STEMI was the most common presentation seen in 44 (62.8%) subjects. Single-vessel involvement was seen in 67 (95.7%) patients. Significant stenosis, i. e., >70% luminal narrowing was seen in 40 (57.1%) patients. Root cause analysis (RCA) is the most common artery to be involved with 35 (50%) cases. Majority of the cases, i.e., 60 (85.7%) cases had thrombolysis in myocardial infarction 3 flow. The majority was managed conservatively. Percutaneous transluminal coronary angioplasty (PTCA) was done successfully in 18.5% of patients. Conclusion: Indian subjects, as observed in this study, differ significantly in their profile compared to the Western population. Indian subjects are predominantly middle-aged males with a significant proportion having traditional risk factors, and they tolerate thrombolysis better, success rates of PTCA are much higher, RCA is the most commonly involved artery as opposed to left anterior descending in Western population and more than half of the patients have atherosclerotic disease involving other arteries.